Building Masters, Tradition, and Terminology in the Vernacular Architecture Around Lower Orontes (Asi) Basin in Hatay Province - Ender Özbay (Sanat Tarihi Yıllığı)
This study aims to document, examine, and evaluate the intangible data regarding the traditional architectural culture in the region that can be defined as the rural environment of Antakya, the central district of Hatay province on the Eastern Mediterranean coastline. This study has been carried out in the field from time to time since 2006 and is based on data obtained through research, interviews, and oral history studies. The compiled data on the actors in traditional architecture (i.e., architects and building masters) and the intangible components of architectural culture (i.e., terminology and building traditions)around Antakya are classified and presented in two large tables, one including 29 names of architects and masters and related information, and the second with 123 terms and idioms and their explanations. During the study, the researcher paid attention to having the people interviewed about terminology be above a certain age; not have been affected by different cultures, languages and traditions outside their own region; not be active users of technological communication opportunities; and be predominantly people who are engaged in activities and have knowledge related to the field of building and construction. Thus, the study has attempted to reach true information, terms, and idioms belonging to the tradition. Some of the architects and craftsmen mentioned in this compilation are understood to have actively worked between the late-19th and mid-20th centuries. The terms compiled in this study have been compared to the terms concerning traditional folk building art from the surrounding city centers, such as from Mersin, Adana, Gaziantep, Şanlıurfa, and Aleppo. The names, activities, and terminology of the architects who were compiled and evaluated suggest that traditional architecture in the region had the characteristics of a school that possessed and transmitted certain standards. In particular, the terminology is worth emphasizing as an important indicator of whether such a specifically qualified professional specialization had existed.